CONCEPT OF FITNESS IN THE OPINION OF STUDENTS FROM THE PHYSICAL EDUCATION AND SPORTS FACULTY OF TIMIȘOARA - Mihaela FAUR; Corina Marina PANTEA (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Fitness is a concept that refers to physical activities meant to create an optimal physical, mental and emotional state for social integration. Today fitness's types can become life styles. The aim of this paper is to analyze the distribution of students opinions from the Faculty of Physical Education and Sports Timișoara, regarding the theoretical knowledge about the concept of fitness in order to achieve a complex research and development of specific fitness programs for different age groups. Hypothesis. It is assumed that the students from the Faculty of Physical Education and Sports Timișoara have a healthy lifestyle. It is assumed that the 149 students have theoretical knowledge about fitness. Using the inquiry method and applying a questionnaire with 26 items, we obtained data related to the theoretical knowledge about fitness and the lifestyle of the 149 respondents. Processing the responses about personal data and anthropometrical measurements we found that the mean age of the respondents is 21.2 years, the mean height of the group is 172.86 cm, the mean weight of group is 65.91 kg. and that 65 of the respondents are female - 48% - and 84 are male - 52%. The 149 respondents have given 285 answers as follows: maintaining and improving health -102 responses - 38.5 % ; muscle toning - 73 answers - 25.6 % ; weight loss - 31 answers - 10.9 % ; increasing physical condition - 76 answers - 27.7 . From 149 respondents, 57 ( 38.3 %) practice fitness, 21 ( 14.1 ) do not practice and 71 ( 47.7% ) practice sometimes and referring to the periodicity of practicing, the answers were: daily - 12 ( 8.1 % ) ; 3-5x / wk. - 40 (26.8% ) 1-2x / wk. -39 ( 26.2 %) ; several times / month -35 ( 23.5 %) ; 1 time / month - 23 ( 15.4 %). The most often used forms of fitness are: jogging (14.2 %), body-building (12%), swimming - aqua-gym (12%). The analysis of all the items led us to the following conclusions: the interviewees consider fitness an activity that leads to a state of well-being, determines a positive attitude and eventually becomes a necessity; fitness can help improve the physical aspect, can remodel the body, and create a psychical comfort state.